Blending Spatial Information Management Technologies and Participatory Approaches to Develop Land Use Plans for Community-Based Natural Resources Management: A Case of Keiyo and Marakwet Districts, Kenya - Muchemi, J. G.; Ucakuwun, E. K.; Greijn, H.; Mungai, Wangu (Africa Environmental Review Journal, 2015)
This paper describes how ‘Modern Spatial Information Technologies’ has been blended with Participatory Approaches to yield ‘Participatory-GIS as a tool, process and practice for use in facilitating the preparation of participatory land use planning at local levels in Kenya. The resulting plans have been used to guide community-based natural resource management among rural-based communities in Keiyo and Marakwet Districts in the Rift Valley Region. While GIS and Remote Sensing techniques provided scientific methodologies for generating reliable land use planning data, participatory approaches enhances consultation and participation of local communities that leads to broad community support for the development agenda, plans and actions. If well applied, Participatory-GIS can become an indispensible practice for empowering local communities to actively participate in social, economic and political that configures how development resources are allocate, accessed and utilized.. Given that participatory-GIS was a new tool and practice to guide participatory land use planning among local community and government staff, its introduction was systematically organized to not only demonstrate the ease of applying it but also to explicitly show its value-addition to the traditional land use planning approaches while enhancing enthusiasm among the development practitioners to catalyze its adoption in similar and other development initiatives. The technical part of the planning process consisted of three steps. The first step included the use of participatory rural appraisal (PRA) approaches and tools to inventory natural resources, document seasonal calendar the availability of the resources and required gender differentiated labor, and establishing of multi-temporal resources use trend. The second step entailed the use of Participatory-GIS approach and technologies in mapping out the resource. This included: sourcing for aerial photographs of 1991 and conducting an aerial photography to acquire images of year 2000; delineating the land cover types from the aerial photos, and a combination of visual and GIS-supported interpretation and analysis of land cover types and land cover changes over the ten years (1991- 2000) of land use. The third step involved the use of the derived spatial data and information products to develop land use plans. This entailed further consultations with the communities to document their community based natural resource management needs; validation of their past and current land uses and trends as depicted from the aerial photograph interpretation and GIS analysis, documenting any social, cultural, economic and political impacts resulting from the 10 years of land use, and developing plans address any issues arising from the ten-years of land use. Results show that communities are able to use devolved remotes sensing and GIS technologies such as aerial photo-enlargements to generate crucial data and information for guiding land use planning process. In addition, Participatory-GIS proved a vital tool and practice of narrowing the gap between development technocrats and local community as it provides a commonly understood pictorial, graphical and illustrative language thus improving consultation and participation. Conversely, if not well planned and facilitated, participatory-GIS like other traditional approaches can fail to reach out to minority community groups who might already be structurally marginalized and discriminated by the dominant society and the state decision making mechanisms. The communities are able to participate in the formulation and implementation of a better land use policy and guidelines, making projections on the utility of land and natural resources, identify future development pressure points and areas, and implement effective land use plans for effective regional development.